DESIGNING FOR FRESHNESS: THE ROLE OF GRAPHIC DESIGNERS IN NIGERIA’S FRUIT PACKAGING INDUSTRY - Ayodele, A. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
In Nigeria’s growing agricultural economy, fruit packaging plays a pivotal role in preserving product quality, ensuring market competitiveness, and influencing consumer perception. While much attention has been paid to food safety and logistics, the role of graphic designers in shaping the visual and functional identity of fruit packaging remains under-explored. This study investigates how graphic design influences freshness perception, branding, and marketability of fresh fruit in Nigeria. Using a qualitative research approach, data were collected through semi-structured interviews with 35 stakeholders across Lagos, Ibadan, Abuja, and Enugu, including graphic designers, fruit vendors, agribusiness professionals, packaging manufacturers, and regulatory officials. Field observations and photographic documentation of packaging practices were conducted in open markets, supermarkets, and design studios. Thematic content analysis revealed that design elements such as color, typography, and cultural motifs significantly influence consumer trust and perceived freshness. However, barriers such as limited access to design expertise, material constraints, and low awareness among producers hamper the effective integration of graphic design in packaging systems. The study highlights the need for greater collaboration between designers and agricultural stakeholders, as well as the establishment of design-informed standards in food packaging. The findings contribute to the discourse on agro-industrial innovation, emphasizing the untapped potential of graphic designers in enhancing value addition, food safety, and export readiness in Nigeria’s fruit sector.